STUDENTS’ EXPERIENCES OF INTERACTION WITH THE SUPERVISORS DURING THE TRANSITION TO CLINICAL CLERKSHIPS - Dian Puspita Sari; Yoga Pamungkas Susani; Dewi Suryani; Emmy Amalia (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Transition to clinical clerkships involves significant changes for students in terms of learning environment and approach to learning. As clinical supervisors, doctors are one of the essential learning resources who also provide access for participation in a clinical environment. This study explored undergraduate medical students’ experiences during the transition to clinical clerkships to understand how these experiences affect their learning.This paper aims to report factors affecting students’ interaction with supervisors during the transition period.Method: This was a qualitative phenomenological study. Participants were selected purposely to represent gender and group of student rotations. Eight 4th year medical students (five female, three male) submitted audio diaries during their first 12 weeks of clinical clerkships. Forty-six of the 73 audio diaries collected in the study contained interactions with supervisors, and these interactions were captured in 76 excerpts.Results: Six themes emerged regarding factors affecting the interaction: (1) characters of the supervisors including the willingness to teach, showing concerns, asking questions to test comprehension, inviting explicitly; (2) supervisors’ workload; (3) students’ clinical knowledge and skills; (4) students’ initiatives: actively participating, asking questions; (5) curriculum and organization: the chance to do mutual interaction (i.e.,mini-CEX), clarity of students’ roles and educational goals; (6) senior peers.Conclusions: Interactions between students and supervisors during the transition to clinical clerkships were influenced by factors internal to both parts and external factors like curriculum and organization, workload,and the presence of senior peers. However, during this phase, where students had not developed a situational understanding of the new environment, supervisors’ characters strongly influenced the interactions through the provision of affective support.